Sulfur-tolerant natural gas reforming for fuel-cell applications - Hennings, Ulrich (KIT Scientific Publishing, 2010)
An attractive simplification of PEM-FC systems operated with natural gas would be the use of a sulfur tolerant reforming catalyst, but such a catalyst has not been available thus far. In this work it is demonstrated that a tailor made rhodium catalyst retains useful activity for typical sulfur levels in the feed. A brief economic comparison showed however that this alternative process is still less economical than the traditional process employing removal of sulfur components by adsorption.